Transcending Written Constraints: Attending to Vitality Through Photography in Pedagogical Documentation - Baeza Hidalgo, Catalina (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2025)
This paper explores the dissonance between intention and implementation in the practice of pedagogical documentation, where early childhood educators display written, polished, and concluded learning events to meet expectations of completion rather than inquiry. It explores how photography and multimodal approaches can reconceptualize pedagogical documentation as a processual practice that attends to what is not yet formed in learning experiences rather than rushing to categories, interpretation, and conclusion. Pedagogical documentation’s meaning making emerges in the act of encounter. When embraced through multimodalities such as visual, performative, oral, and embodied languages, it becomes a generative force rather than a static representation. Through the weaving of photos into this paper, photography is examined as an act of relational mutuality rather than a practice that tends to isolate learning events from their web of relations and then reflect on them disconnected from the very relationships that give them meaning. In this way, the author argues that pedagogical documentation becomes an ethical form of attention that resists reductionist approaches when attending to learning still in nascent form. This paper grapples with conventional pedagogical documentation practices that privilege written narratives and photographs as extractions—as if learning could be captured and held still—and opens toward a relational, emergent approach that keeps pedagogical moments alive and living.